THE FIGHT AGAINST DRUG TRAFFICKING IN EAST ASIA - MUSAEV, Djamaliddin (Journal of Fundamental Studies, 2023)
The article examines the policy of the ASEAN countries, China, Japan and the Republic of Korea in relation to the fight against the spread of drugs of synthetic origin. The 2020 US Department of State Strategic Report on International Drug Control was also reviewed to analyze the situation with countering the spread of drugs in East Asia. The article also provides information on each country in East Asia, which allows for a comparative analysis of the anti-drug policy of the states of the region.